Variación de algunas características foliares de Avicennia germinans (L.) L. (Avicenniaceae) en un gradiente climático y de salinidad - Soto, Ricardo (1987)
We discuss the relationship between the size and shape of leaves of Avicennia germinans growing in different climatic and saline conditions. Plants from drier sites and with higher salt concentrations showed a reduction of leaf area and modified general leaf shape. Eliptical-obovate leaves and those abovate with acute-obtuse or obtuse apices were more common in those environments.